Patients’ time perception in the waiting room of an ambulatory emergency unit: a cross-sectional study - Hervé Spechbach; Jessica Rochat; Jean-Michel Gaspoz; Christian Lovis; Frederic Ehrler (BMC Emergency Medicine, 2019)
Abstract Background Patient satisfaction has become an increasingly important element in a service-oriented healthcare market. Although satisfaction is influenced by many factors, the waiting time to be seen by medical staff has been shown to be one of the key criteria. However, waiting is not an objective experience and several factors can influence its perception. Methods We conducted a questionnaire-based, cross-sectional study among patients attending the emergency unit of a Swiss university hospital in order to explore the key factors influencing wait perception. Results A total of 509 patients participated in the study. Appropriate assessment of emergency level by caregivers, the feeling of being forgotten, respect of privacy, and lack of information on the exact waiting time were identified as significant variables for wait perception. Conclusions Our study confirmed the existence of a ‘golden hour’ when the patient is willing to wait until the medical encounter. In case the wait cannot be limited, an appropriate assessment of the emergency level by caregivers and avoiding the patients of feeling being forgotten are very important factors to avoid a negative perception of the waiting time before seeing a doctor. Trial registration (ID REQ-2016-00555).